Diagnostic markers of axonal degeneration and demyelination in sensory nerve conduction. Issue 6 (9th February 2016) - Oh, Shin J.; Hemmi, Shoji; Hatanaka, Yuki
ABSTRACT: Introduction: The aim of this study was to formulate diagnostic hallmarks of axonal degeneration and demyelination in sensory nerve conduction studies (NCS). Methods: We compared nerve conduction data obtained with surface electrode (SE) NCS and on‐nerve needle (ONN) NCS in 50 cases of demyelination and 22 cases of axonal degeneration as assessed by sural nerve biopsy. Results: The overall diagnostic sensitivities of sensory nerve conduction were 26% by SE‐NCS and 69% by ONN‐NCS. The most helpful marker for demyelination was negative‐peak nerve conduction velocity (NP‐NCV), using a 36% decrease from the means in both techniques. Dispersion was also helpful in identifying demyelination. Low amplitude and absence of compound nerve action potential were indicative of general pathology in SE‐NCS but of axonal degeneration in ONN‐NCS. Conclusion: Although diagnostic sensitivity is low, NP‐NCV and dispersion can be used for diagnosis of demyelination in sensory NCS. Muscle Nerve 53 : 866–871, 2016